Peran Inspektorat Dalam Penerapan Sistem Pengendalian Intern Pemerintah Di Pemerintah Daerah Kabupaten Pekanbaru - Syamsuwir Syamsuwir; Yusri Munaf (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2020)
The Inspectorate as the Government Internal Supervisory Apparatus is one of the important elements of government management in order to realize good governance that leads to a clean government / bureaucracy and the implementation of effective, transparent, accountable and free governance from KKN practices . The internal control system plays a key role in realizing financial accountability. Weaknesses in the financial system of government agencies so far occur because of the weak design and implementation of internal control systems. The Government has provided guidance on how Government Agencies operate the Internal Control System through Government Regulation (PP) Number 60 Year 2008) concerning the Government Internal Control System This research is a qualitative research with an exploratory approach. Choosing respondents through sampling techniques with a purposive sampling method. Data collection techniques through interviews, observation and documentation study. Interviews are transcribed into data transcripts, then analyzed, coded, and categorized into themes. The data analysis technique uses content analysis which is analyzed according to the topic and identifies into several topics. The results showed that the role of the Inspectorate in the implementation of SPIP in Pekanbaru City was in terms of internal supervision and assurance namely audit, review and evaluation. In addition, the Inspectorate also acts as an early warning provider, as a driver, as a companion and as a consultant. The main obstacles faced by the Inspectorate in carrying out these roles are commitment and competency constraints, while other obstacles are SPIP involving many parties, documentation and archiving in each OPD that is not optimal, lack of socialization related to SPIP, high turnover rates in the City Government Pekanbaru, APIP quantity and quality constraints and facilities and infrastructure constraints. The Inspectorate has made efforts to overcome obstacles including providing outreach to DPOs, increasing the competence of APIP, improving facilities and infrastructure.